Penggunaan Kitosan dari Kulit Udang dalam Menurunkan Kadar Total Suspended Solid (TSS) pada Limbah Cair Industri Plywood - Harahap, Sampe (Jurnal Perikanan dan Kelautan, 2016)
This research was conducted in the laboratory of waste Processing Technology and the laboratory of Water Quality Management in the FAPERIKA – UNRI. The aim of this research is to identify the ability of chitosan in reducing the level of TSS in the wastewater of plywood industry. The method used in this research is  experimental study with completely randomized design, one factor, 4 level, 12 units of trial. Several concentration of chitosan such as 0 mg/L, 15 mg/L, 30 mg/L were applied on the wastewater and observed after 8 hours, 12 hours and 16 hours. The result shown that 12 hours after addition of 30 mg chitosan /L, the quality of the waste improved : TSS 182,3 – 56,7 mg/L, Phenol 2,4 - 0,5 mg/L, BOD5 132-93 mg/L, COD 279-217 mg/L and pH 6 - 9.